2004
DOI: 10.1007/s00436-004-1187-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and antibody production during the course of resolution in Plasmodium yoelii 17XL-infected BALB/c mice treated with febrifugine and isofebrifugine mixture from leaves of Hydrangea macrophylla var. Otaksa

Abstract: Cytokine and antibody production was investigated during the course of resolution of primary infection in Plasmodium yoelii 17XL-infected BALB/c mice treated with a mixture of febrifugine and isofebrifugine. The infected mice in an untreated control group showed a progressively increasing parasitemia, leading to mouse death. In contrast, infected mice given the mixture orally showed low parasitemia levels during administration. Following a transient increase in parasitemia in the bloodstream of the treated mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Doses of 10 mg/kg of febrifugine had previously been associated with toxicity and subsequent mortality of mice [15]. However, a 5-day oral dosage of 1 mg/kg of the febrifugine and isofebrifugine mixture showed parasite clearance and no mouse mortality [16]. In the present study, autopsy of mice treated with bud-extracts showed gross hepatotoxicity (data not shown).…”
Section: In Vivo Antimalarial Testmentioning
confidence: 50%
“…Doses of 10 mg/kg of febrifugine had previously been associated with toxicity and subsequent mortality of mice [15]. However, a 5-day oral dosage of 1 mg/kg of the febrifugine and isofebrifugine mixture showed parasite clearance and no mouse mortality [16]. In the present study, autopsy of mice treated with bud-extracts showed gross hepatotoxicity (data not shown).…”
Section: In Vivo Antimalarial Testmentioning
confidence: 50%
“…In a nonlethal P. yoelii infection, IgG2 was previously reported to be predominant, although both IgG1 and IgG3 were present during the primary infection (Langhorne et al 1984). As for fatal malaria infections in mice, the low burden of parasites induced by drug treatment may trigger a production of protective parasite-specific antibodies which clear all parasites from peripheral blood at the later phase of infection (Ishih et al 2004;Langhorne et al 1989;Stevenson and Tam 1993). In the present study, the titers of the parasite-specific IgG1 and IgG2a of the infected 129S1 mice elevated significantly from day 15 pi; elevations which were corresponding with the onset of decrease in parasitemia.…”
Section: Discussionmentioning
confidence: 95%